LQR of Periodic Review Perishable Inventory Systems for Radioisotope Luthesium-177 - Munawwaroh, Dita Anies (Prosiding Konferensi Nasional Penelitian Matematika dan Pembelajarannya, 2017)
This research is about inventory system with periodic review policy. It will be controlled with linear quadratic regulator to keep the inventory level. This optimal control uses discrete time and has quadratic equation for objective function and linear equation for the constraint. The inventory system must be satisfy the assumption that it has single supplier, perishable goods, has a lead time, but the inventory system is not allowed lost sales. As a case study on simulation, the author will apply to optimize the inventory systems of radioisotope Luthesium-177. Because Luthesium-177 is a perishable goods that has a half-life 6,71 days. The uses of Luthesium-177 as cancer therapy to destroy cancer cells.